Syntheses, Li Insertion, and Photoactivity of Mesoporous Crystalline TiO2 - Yue, Wenbo; Randorn, Chamnan; Attidekou, Pierrot S.; Su, Zixue; Irvine, John T. S.; Zhou, Wuzong (Advanced functional materials, 2009)
Ordered mesoporous rutile and anatase TiO2 samples are prepared using mesoporous silica SBA‐15 as template and freshly synthesized titanium nitrate and titanium chloride solutions as precursors. The rutile material formed from the nitrate solution is monocrystalline and contains minimal amounts of Si with a Si:Ti ratio of 0.031(4), whereas the anatase material formed from the chloride solution comprises nanocrystals and contains a higher content of Si with a Si:Ti ratio of 0.18(3). It is found that control of temperature and selection of Ti‐containing precursor play important roles in determining the crystal phase and crystallinity. A possible formation mechanism of porous crystalline TiO2 is suggested. Characterization of these porous materials is performed by XRD, HRTEM, and nitrogen adsorption/desorption. SBA‐15‐templated mesoporous rutile TiO2 exhibits a higher Li ion insertion capability than KIT‐6‐templated TiO2 due to its larger surface area. Likewise mesoporous anatase TiO2:SiO2 composite has a better photoactivity than bulk TiO2 or TiO2‐loaded SBA‐15 for bleaching methylene blue. Porous monocrystalline and polycrystalline TiO2 materials are fabricated using mesoporous silica SBA‐15 as template and characterized using XRD, HRTEM, and nitrogen adsorption/desorption. A high level of Li insertion, 1.06 Li per TiO2 unit, is demonstrated in porous rutile TiO2. The photoactivity of silica‐containing porous polycrystalline anatase is also investigated.